O'Reilly book club audio collection 2023 - Ramalho, Luciano; Ford, Neal; Richards, Mark; Freeman, Eric; Robson, Elisabeth; Newman, Sam; Kleppmann, Martin; Géron, Aurélien (O'Reilly Media, Inc., 2023)
Look no further for the 2023 audio-only collection of O'Reilly Book Club interviews. Hear directly from our authors about their book writing processes and gain insight into how they've become the subject matter experts in their fields.